If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2b = 2 + -3b Solving 4 + -2b = 2 + -3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3b' to each side of the equation. 4 + -2b + 3b = 2 + -3b + 3b Combine like terms: -2b + 3b = 1b 4 + 1b = 2 + -3b + 3b Combine like terms: -3b + 3b = 0 4 + 1b = 2 + 0 4 + 1b = 2 Add '-4' to each side of the equation. 4 + -4 + 1b = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 1b = 2 + -4 1b = 2 + -4 Combine like terms: 2 + -4 = -2 1b = -2 Divide each side by '1'. b = -2 Simplifying b = -2
| 1.4x*1000= | | 2x+84=3.33333333 | | 2x+84=3.333333 | | 9-2c=-9+7c | | 12-7x=6-x | | 4(w+5)-7w=38 | | 3.6=-2.9+5.8 | | 1/4-9=12 | | 3.6=-29+5.8 | | -3-j=-9-2j | | 9.10=k+7.10 | | (3x-4)-(6x+3)+(9x-4)= | | 2/x=18/27 | | 9h-3=10h | | 12+3q= | | (4x+1)+(x-1)+(x+1)=180 | | T-3=9 | | t^2+3r-2=0 | | -10-6w=-8w | | 2X+2-(4X-1-9X)=6X-1 | | 19-m=23 | | -7y+5y=-10+6 | | -2n+7=-n | | 3*(-1/2)(4^2)-(-3^3)/-1/2 | | 11x-4=55 | | 4x^2+9x-4=x^2-2x | | Y-5=4(y-5)-9 | | 61-11x=17-8x | | 4r=7+5r | | 16x*9y=214 | | 5(2-0.375)-9(0.125)=4(3-0.25) | | 7/9=1/3t |